Clinical significance of complex karyotype at diagnosis in pediatric and adult patients with de novo acute promyelocytic leukemia treated with ATRA and chemotherapy. Issue 5 (16th April 2019) - Labrador, Jorge; Luño, Elisa; Vellenga, Edo; Brunet, Salut; González-Campos, José; Chillón, Maria C.; Holowiecka, Aleksandra; Esteve, Jordi; Bergua, Juan; González-Sanmiguel, José D; Gil, Cristina; Tormo, Mar; et al.
Abstract: Although additional cytogenetic abnormalities (ACA) do not affect the prognosis of patients with t(15;17) acute promyelocytic leukemia (APL), the role of a complex karyotype (CK) is yet to be clarified. We aimed to investigate the relationship of CK with relapse incidence in 1559 consecutive APL patients enrolled in three consecutive trials. Treatment consisted of AIDA induction followed by risk-adapted consolidation. A CK (CK) was defined as the presence of ≥2 ACA, and a very CK (CK+) as ≥3 ACA. Eighty-nine patients (8%) had a CK, of whom 41 (4%) had CK+. The 5-year cumulative incidence of relapse (CIR) in patients with CK was 18%, and 12% in those with <2 ACA ( p =.09). Among patients with CK+, the 5-year CIR was 27% vs 12% ( p =.003), retaining the statistical significance in multivariate analysis. This study shows an increased risk of relapse among APL patients with CK + treated with ATRA plus chemotherapy front-line regimens.